Fake news? The impact of information mismatch on mating behaviour - Leonor R. Rodrigues; Sara Magalhães (Ecology and Evolution)
Abstract Multiple cues are often used for mate choice in complex environments, potentially entailing mismatches in the information conveyed by different sources. We address the consequences of this information mismatch for receivers using the spider mite Tetranychus urticae, in which virgin females are highly valuable mates compared to mated females, given first male sperm precedence. Accordingly, males are known to prefer virgins and distinguish them using cues from the females themselves and that they leave on the substrate. Whereas cues from females are highly reliable, those left on the substrate may not reflect the real female mating status if females move and/or mate. Here, we tested the consequences of such mismatch by exposing males to mated or virgin females on patches previously impregnated with cues deposited by females of either mating status. Male mating attempts were solely affected by substrate cues while female acceptance and the number of mating events were independently affected by both cues. Copulation duration, in contrast, depended mainly on the mating status of the female, with the number of copulations and the total time spent mating being intermediate in environments with mismatched information. We also show that males incur mating costs, reflected in reduced survival in environments with virgin cues. These results suggest that substrate cues left by females are instrumental for males to find their mates. However, in environments with mismatched information, males may pay survival costs without the associated benefit of mating with virgins, or they may lose opportunities to mate with virgins by responding to substrate cues from mated females. The benefit of using multiple cues will then hinge upon the frequency of information mismatch, which itself should vary with the dynamics of populations.